Evaluation of Exposure to Noise and Vibration and Its Effect on Work-related Fatigue - Rahimimoghadam, Somayeh; Javan, Safoora; Yari, Saeed; Kheyrkhah, Atefeh; Nourmohamadi, Mohammad (Asian Pacific Journal of Environment and Cancer, 2023)
Introduction: Exposure to vibration and noise has been identified to potentially contribute to work-related fatigue, consequently causing a range of adverse effects on job performance. Method: In this study, a sample of 62 city bus drivers underwent examination to evaluate noise levels through the utilization of a TES dosimeter. Additionally, vibration measurements were conducted using an SV 106 vibration meter. Furthermore, the level of occupational fatigue was determined through the utilization of a Swedish fatigue questionnaire. Results: In the conducted study, it was observed that bus drivers were subjected to an average exposure level of 82.18 dB and 0.99 m/s2 for noise and whole-body vibration, respectively, throughout their work shifts. Additionally, their average job fatigue score was measured to be 26.21 out of a total of 200. To comprehensively evaluate the influence of various factors on (WRF), both single-variable and multi-variable analyses were conducted. The result of the univariate tests exhibited a notable association between job fatigue and the Lon life of the vehicle, the type of car seat (spring or inflatable), as well as the level of exposure to vibration and job satisfaction. Moreover, when considering the influencing factors concurrently in the multivariate test, a significant correlation between occupational fatigue and exposure to vibration, as well as the type of chair, was established. Conclusion: Improving the quality of buses by implementing modernized features that minimize vibrations and reduce noise levels can greatly contribute to mitigating fatigue among urban bus drivers.